Lexical-semantics in translation: a combined data-based cognitive approach to the investigation of the semantic relationship of the translations of kèyì - He,Yijia (Nanyang Technological University, 2022)
Many studies of lexical semantics focus on the semantic relations among near-synonyms. Nevertheless, the previous research favored verbs and nouns. The meanings of adjectives and adverbs are hard to explore, as they are modifiers, whose meanings are influenced by the words they modify. This study aims to investigate the semantic relationships among a group of near-synonyms, which are translations of the Chinese word kèyì. Most of them are adverbs. Additionally, this study taps into the association between different dominant languages (Chinese or English) of translators and these translators’ choices of the translations of kèyì. To achieve the first research aim, a survey was done on 28 Chinese and English bilingual translators. Componential decomposition was conducted based on the answers from participants, and then the specifications of the semantic features embedded in the translations of kèyì were produced. The relations among these translations were displayed in hierarchical links. Besides the survey, a corpus-based approach was also adopted. Correspondence analysis was conducted on the collocates of four adverbs selected from the translations of kèyì: deliberately, intentionally, purposely, and sedulously. After the analysis, the collocational similarities and differences of these adverbs were displayed in a graph. Results reveal that intentionally shares the least semantic properties with purposely and deliberately. Such finding contradicts the synonymous relations of them displayed in the WordNet. It is also found out that sedulously is semantically far away from the rest. To reach the second research aim, Fisher’s exact test was applied based on the data yield from the survey. The result suggests that the dominant languages of participants do not affect their translations of kèyì in a significant way. The findings of the collocational similarities and differences of the four adverbs can be applied in the teaching of English as a second language and in the translator training.